Case report: Transmuscular migration of a solid encircling silicone band through all four rectus muscles - Gu, Ruiping; Wu, Kaicheng; Jiang, Chunhui (Frontiers in Medicine, 2025)
PurposeWe present a case of transmuscular migration of a solid encircling silicone band through all four rectus muscles.ObservationsA 33-year-old male with high myopia presented with a progressively worsening subclinical peripheral rhegmatogenous retinal detachment in his left eye. An encircling silicone band (#240) was placed anterior to the equator, and 5-0 polyester sutures (Ethicon, Inc.) were used to secure the band at all four quadrants. Six months later, the encircling band and suture knots were visible under the bulb conjunctiva, close to the limbus in all four quadrants. One and a half years after the retinal detachment surgery, the encircling band was removed because of a mild foreign body sensation. During that surgery, it was noted that the encircling band was located anterior to the insertion of all four rectus muscles. Throughout the entire follow-up period, the position and movement of the left eye remained normal.Conclusion and importanceA deep and long bite of the sclera should be used to secure the silicone band, especially in cases of high myopia and when the band is placed anterior to the equator. Even if the encircling silicone band cheese wire through the four rectus muscles, ocular motility may still remain normal.